In vitro assessment of the nematicidal potential of Streptomyces violascens strain AS2 against root-knot nematodes (Meloidogyne sp.) - Azlay, Latifa; Oubassou, Ez-Zahra; Berr, Alexandre; Mayad, El Hassan; Barakate, Mustapha (Archives of Biological Sciences, 2024)
Paper description: Chemical nematicides are used in plant parasitic nematode management. Due to their harmful impact on the environment, sustainable solutions are needed. Research focused on Actinobacteria which have diverse mechanisms of action. We studied the in vitro effects of Streptomyces violascens extracts on eggs and second-stage juveniles of Meloidogyne Streptomyces violascens has a significant impact on nematode stages. This work advocates the integration of Streptomyces violascens into sustainable agricultural practices, showing its effectiveness as a green solution on a large scale. Abstract: Root-knot nematodes (RKNs, Meloidogyne spp.) present a major challenge to sustainable production. The detrimental environmental impacts and increasing resistance associated with synthetic nematicides have increased the need for biocontrol alternatives. Here, we report for the first time the nematicidal properties of Streptomyces violascens and its viability as a safe and effective solution against nematode infestation. In vitro assays showed that aqueous and ethyl acetate extracts of S. violascens significantly impeded Meloidogyne sp’s reproductive and locomotive functions. The aqueous extract displayed remarkable efficacy, completely inhibiting egg hatching at a concentration of 600 µg/mL, with an LC50 of 168.38 µg/mL, and causing 99% immobility of second-stage juveniles (J2s) at 800 µg/mL within 72 h. Conversely, the organic extract exhibited a 29.3% hatching rate (LC50 of 849.26 µg/mL) and 79% immobility of J2s under comparable conditions. These findings point to the robust nematicidal potential of S. violascens extracts. Enzymatic profiles supported these results, with the selected isolate producing chitinase and protease enzymes capable of degrading nematode eggshells. Our results show that the S. violascens strain can be integrated into a sustainable nematode management practice as an important agent of RKN biocontrol.